Effect of Pyrolysis Temperature on PhysicoChemical Properties and Acoustic-Based Amination of Biochar for Efficient CO2 Adsorption - Chatterjee, Riya; Sajjadi, Baharak; Chen, Wei-Yin; Mattern, Daniell L.; Hammer, Nathan; Raman, Vijayasankar; Dorris, Austin (Frontiers in Energy Research, 2020)
The present study examined the effect of pyrolysis temperature on the physicochemical properties of biochar, activation process and carbon capture. Two different categories of biochars were synthesized from herbaceous (miscanthus and switchgrass) and agro-industrial (corn stover and sugarcane bagasse) feedstock under four different pyrolysis temperatures −500, 600, 700, and 800°C. The synthesized biochars underwent sono-amination activation comprising low-frequency acoustic treatment followed by amine functionalization to prepare adsorbents for CO2 capture. The highest increment (200%) of CO2 capture capacity was observed for sono-aminated samples prepared at 600 and 700°C (maximum improvement for miscanthus), while biochars synthesized at 500 and 800°C demonstrated comparatively lesser increment in adsorption capacities that falls in the range of 115–151 and 127–159%, respectively compared to 600 and 700°C. The elevated pyrolysis temperature (particularly 600 and 700°C) resulted in increased %C and %ash contents and reduced %N contents with enhancement of micro surface area and pore volume. Thus, the superior adsorption capacity of miscanthus (at 600 and 700°C) can be attributed to their large surface areas (303–325 m2/g), high carbon contents (82–84%), and low ash contents (4–5%), as well as %N contents after sono-amination that was twice that of raw char.